The Impact of Incentives and Work Discipline on Teacher Performance in Tanjung Lago Junior High Schools - Natalia, Dessy; Ahyani, Nur; Djunaidi, Djunaidi (Journal of Social Work and Science Education, 2025)
This quantitative study examines the effects of incentives and work discipline on teacher performance in Tanjung Lago District, Banyuasin. This study was conducted at SMP Negeri Sekecamatan Tanjung Lago Kabupaten Banyuasin. In this study, using quantitative research methods. The methods used are correlation test methods and partial and simultaneous tests. Using a Likert-scale questionnaire administered to 82 teachers, data were analyzed via SPSS 26. Results indicate that incentives (45.3%) and work discipline (47.4%) significantly enhance teacher performance. The findings underscore the importance of fair incentive systems and strict work discipline in improving educational outcomes. There is a significant effect of incentives and work discipline on the performance of junior high school teachers in Tanjung Lago sub-district. The conclusion is that there is a significant effect of incentives and work discipline on the performance of teachers in Tanjung Lago sub-district.